Rights protection in prisons: Understanding recommendations-making by prison inspection and monitoring bodies in the European Union - Aizpurua, Eva (Punishment & society, 2021)
Despite the increasing focus on prison inspection and monitoring bodies in international law and policy, little is known about their operations in practice. This study contributes to fill this gap by examining how countries of the European Union (EU) have responded to these demands, paying special attention to one of the central tasks of these bodies: the making of recommendations. To do so, we used data from the first EU-wide survey of prison oversight bodies, with responses from all Member States. Our findings reveal that recommendations-making is a key part of the work of these bodies. They also provide evidences that the approach to dialogue between these bodies and prison authorities advocated in the legislation is taking place on the ground.